A universal interface for plug-and-play assembly of stretchable devices - Jiang, Ying (2023)
Stretchable hybrid devices have enabled high-fidelity implantable1-3 and on-skin4-6 monitoring of physiological signals. These devices typically contain soft modules that match the mechanical requirements in humans7,8 and soft robots9,10, rigid modules containing Si-based microelectronics11,12 and protective encapsulation modules13,14. To make such a system mechanically compliant, the interconnects between the modules need to tolerate stress concentration that may limit their stretching and ultimately cause debonding failure15-17. Here, we report a universal interface that can reliably connect soft, rigid and encapsulation modules together to form robust and highly stretchable devices in a plug-and-play manner. The interface, consisting of interpenetrating polymer and metal nanostructures, connects modules by simply pressing without using pastes. Its formation is depicted by a biphasic network growth model. Soft-soft modules joined by this interface achieved 600% and 180% mechanical and electrical stretchability, respectively. Soft and rigid modules can also be electrically connected using the above interface. Encapsulation on soft modules with this interface is strongly adhesive with an interfacial toughness of 0.24 N mm-1. As a proof of concept, we use this interface to assemble stretchable devices for in vivo neuromodulation and on-skin electromyography, with high signal quality and mechanical resistance. We expect such a plug-and-play interface to simplify and accelerate the development of on-skin and implantable stretchable devices.